Prognosis of shoulder tendonitis in repetitive work: a follow up study in a cohort of Danish industrial and service workers. Issue 9 (22nd August 2003) - Bonde, J P; Mikkelsen, S; Andersen, J H; Fallentin, N; Baelum, J; Svendsen, S W; Thomsen, J F; Frost, P; Thomsen, G; Overgaard, E; Kaergaard, A; ,
Abstract : Background: The physical and psychosocial work environment is expected to modify recovery from shoulder disorders, but knowledge is limited. Methods: In a follow up study of musculoskeletal disorders in industrial and service workers, 113 employees were identified with a history of shoulder pain combined with clinical signs of shoulder tendonitis. The workers had yearly reexaminations up to three times. Quantitative estimates of duration, repetitiveness, and forcefulness of current tasks were obtained from video recordings. Perception of job demands, decision latitude, and social support was recorded by a job content questionnaire. Recovery of shoulder tendonitis was analysed by Kaplan-Meier survival technique and by logistic regression on exposure variables and individual characteristics in models, allowing for time varying exposures. Results: Some 50% of workers recovered within 10 months (95% CI 6 to 14 months). Higher age was strongly related to slow recovery, while physical job exposures were not. Perception of demands, control, and social support at the time when the shoulder disorder was diagnosed, were associated with delayed recovery, but these psychosocial factors did not predict slow recovery in incident cases identified during follow up. Conclusion: The median duration of shoulder tendonitis in a cross sectional sample of industrial and service workers was in the order of 10 months. This estimate is most likely biased towards too high a value. Recovery was strongly reduced in higher age. Physical workplace exposures and perceived psychosocial job characteristics during the period preceding diagnosis seem not to be important prognostic factors.